Commercial and industrial consumers' perspectives on electricity pricing reform: Evidence from India. (July 2019) - Moerenhout, Tom S.H.; Sharma, Shruti; Urpelainen, Johannes
Abstract: This paper investigates the perspectives of commercial and industrial consumers on electricity pricing reform in Uttar Pradesh, India. In a first study of its kind, we report results from semi-structured, in-depth interviews that were conducted with a variety of firms, based on their electricity price dependence and employment. Results show that senior management officials already strongly oppose cross-subsidy policies in which they pay higher tariffs to reduce prices for households and farmers. Firms also have very few available coping mechanisms to deal with further electricity tariff rises. Senior management officials believe their firms will have to compromise on electricity usage if prices are increased again. Available models suggest that this will likely be a cause for lowering output and overall machine and labor productivity. While firms do expect price rises in the short term, they believe this will impact their productivity and have a low opinion of the state government. This might be aggravated by little knowledge about the price setting mechanism, their means of participation and the level of utility dependence on state subsidies. Highlights: Interviews of commercial and industrial electricity consumers in Uttar Pradesh, India. Respondents strongly oppose cross-subsidy policies that increase their electricity prices. Respondents have few mechanisms for coping with electricity price increases.